LEAN MANAGEMENT THROUGH DIGITAL TRANSFORMATION: CHALLENGES AND OPPORTUNITIES FOR THE ENERGY AND PUBLIC UTILITIES INDUSTRY - ANGELOPOULOS, Michail K.; KONTAKOU, Christina A.; POLLALIS, Yannis A. (Journal of Advanced Research in Management; Vol 10 No 2 (2019): JARM Volume X Issue 2(20) Winter 2019, 2020)
In an era of increasing technological transformation, industries, competitors, and companies are combining platforms to create unique methods for engagement. Survival and growth in a rapidly changing marketplace require companies to embrace internal innovation that adds value for both channel members and customers. The fourth industrial revolution has already begun to take shape, on the road to an end-to-end value chain, by using Industrial Internet of Things (IIoT) and decentralized intelligence in manufacturing, production and logistics. The world is heading toward a digitized future. Already, an entire generation has grown up immersed in the digital world. This paper focus on the following fields: general strategy and procedural aspects of digital transformation, digital transformation and lean, lean digital management, applying lean digital transformation and transformation of enterprise resource planning systems to smart engaged systems. finally, this research studies the challenges of digital transformation in energy industry of utilities.